Caracterização eletroquímica de eletrodos de diamante dopado com boro em função de seu pré-tratamento - Carvalho, Adriana Evaristo de (2007)
The effect of galvanostatic electrochemical pre-treatments on the surface composition and wettability of boron-doped diamond (BDD) electrodes was characterized by X-ray photoelectron spectroscopy (XPS) analyses and contact angle measurements, respectively. The smallest wettability was presented by the least doped as-received BDD electrode; however, the wettability of all the BDD electrodes increased after the cathodic and anodic pre-treatments. From the XPS analyses, an increase in the surface O/C ratio after the anodic pre-treatment was observed, which was attributed to the introduction of carbon-oxygen functionalities on the surface of the BDD electrodes. The effects of the current and charge densities applied on the BDD electrodes, during the cathodic and anodic pre-treatments, were evaluated through the redox reactions of the Fe(CN)6 3-/4- couple by cyclic voltammetry and by electrochemical impedance spectroscopy. The high sensitivity of the electrochemical and electrical properties of this redox couple to the surface terminations of the BDD electrodes was confirmed; the redox reaction kinetics are much faster after cathodic pre-treatments. The electrical properties presented by the BDD electrodes after anodic pre-treatmens, characterized by a resistive response in intermediate frequencies, have been explained as due to a possible partial blocking of the surface, which would be associated to the presence of carbon-oxygen functionalities on the electrodes surface. On the other hand, the electrochemical and electrical properties were shown to be controllably modulated through the galvanostatic electrochemical pretreatments. Studies on these properties were also carried out for the Fe3+/2+ and Ru(NH3)6 3+/2+ redox couples. For the former, contrary to that for the xxiv Fe(CN)6 3-/4- couple, the charge transfer kinetics (slow) become faster after anodic pre-treatments, instead of after cathodic pre-treatments. In the case of the Ru(NH3)6 3+/2+ redox couple, the electrochemical behavior is independent of the electrode surface state, the same being true for the electrical properties, whose use to evaluate the quality of BDD electrodes is proposed. Finally, studies on the ferrocenecarboxylic acid redox species in non-aqueous medium (acetonitrile), in the absence and after additions of water (or glycerol), were carried out in order to investigate the nature of the surface partial blocking of anodically pre-treated electrodes, in the presence of redox couples such as Fe(CN)6 3-/4- or ferrocene. The obtained results indicate that such partial blocking is due to the adsorption of water molecules, by hydrogen bonding with the carbon-oxygen functionalities. This partially prevents the access of the redox reaction to electrochemically active sites, thus explaining why much smaller charge transfer reaction rates are attained when anodically pre-treated electrodes are used.